Switchable photoluminescence liquid crystal coated bacterial cellulose films with conductive response - Tercjak, Agnieszka; Gutierrez, Junkal; Barud, Hernane S. [UNESP]; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2016)
Three different low molecular weight nematic liquid crystals (LCs) were used to impregnate bacterial cellulose (BC) film. This simple fabrication pathway allows to obtain highly transparent BC based films. The coating of BC film with different liquid crystals changed transmittance spectra in ultraviolet-visible region and allows to design UVC and UVB shielding materials. Atomic force microscopy results confirmed that liquid crystals coated BC films maintain highly interconnected three-dimensional network characteristic of BC film and simultaneously, transversal cross-section scanning electron microscopy images indicated penetration of liquid crystals through the three-dimensional network of BC nanofibers. Investigated BC films maintain nematic liquid crystal properties being switchable photoluminiscence as a function of temperature during repeatable heating/cooling cycles. Conductive response of the liquid crystal coated BC films was proved by tunneling atomic force microscopy measurement. Moreover, liquid crystal coated BC films maintain thermal stability and mechanical properties of the BC film. Designed thermoresponsive materials possessed interesting optical and conductive properties opening a novel simple pathway of fabrication liquid crystal coated BC films with tuneable properties.
Keywords: Bacterial cellulose; Conductive properties; Nematic liquid crystals; Photoluminescence properties; UV shielding